COVID-19 in patients with acute lymphoblastic leukemia - T. S. Chudnova; E. N. Misyurina; E. A. Baryakh; T. N. Tolstykh; L. T. Shimanovskaya; D. E. Gagloeva; E. I. Zhelnova; A. B. Makeshova; K. V. Yatskov; E. N. Zotina; D. D. Ivanova; M. A. Mingalimov; et al. (Онкогематология)
Background. Patients with acute lymphoblastic leukemia (ALL) have been the most vulnerable group of patients at risk of severe and extremely severe COVID-19 throughout the coronavirus pandemic. Secondary immunodeficiency due to acute leukemia, as well as antitumor treatment, predisposes to the development of a more severe infection, as well as long-term SARS-CoV-2 persistence even after complete regression of COVID-19 symptoms. Thus, although after the emergence of the SARS-CoV-2 Omicron variant, coronavirus infection began to occur predominantly in a mild form, COVID-19 in ALL patients remains an urgent problem.Aim. To assess hospital survival of patients with ALL and concomitant coronavirus infection, to identify predictors of death and to evaluate the impact of program antitumor therapy on the outcome in this cohort of patients.Materials and methods. A retrospective analysis of ALL patients hospitalized in City Clinical Hospital No. 52 with coronavirus infection from February 2020 to December 2022 was conducted. Diagnosis and treatment of patients were carried out in accordance with valid at the time of hospitalization temporary guidelines “Prevention, diagnosis and treatment of new coronavirus infection (COVID-19)”. Univariate and multivariate regression analyses were performed to identify predictors of mortality in patients with ALL and COVID-19. Survival analysis was performed using the Kaplan–Meier method. A p <0.05 was considered statistically significant.Results. The study included 60 patients with ALL and concomitant coronavirus infection (30 men and 30 women). The median age was 42 years. Extremely severe coronavirus infection was observed in 25 % of patients in 2020–2021 and in 5 % of patients in 2022. Forty five patients received chemotherapy a month before hospitalization for COVID-19, 23 patients – during hospitalization. In-hospital mortality was 25 % (11 patients in 2020, 4 patients in 2021). The cause of death in 9 (60 %) cases was severe coronavirus infection; 4 (27 %) patients died as a result of severe bacterial complications, 2 (13 %) – due to ALL progression. In multivariate regression analysis, the following predictors had a statistically significant impact on the outcome: ALL relapse, absence of seroconversion at the time of outcome (anti-SARS-CoV-2 IgG level at the time of outcome <50 U/mL). When analyzing the impact of chemotherapy administered a month before or during hospitalization due to coronavirus infection, statistically significant values were not obtained for any of the factors.Conclusion. Considering the obtained results and international recommendations for the treatment of ALL patients with COVID-19, the decision on antitumor treatment for ALL patients when SARS-CoV-2 RNA is detected by polymerase chain reaction in an oropharyngeal swab should be made individually depending on the patient’s age, clinical manifestations of coronavirus infection, ALL status and the antitumor therapy phase. In addition, given the reduced antiviral response in ALL patients, special attention should be paid to the prevention of SARS-CoV-2 infection, and in case of disease development, passive immunization methods (virus-neutralizing monoclonal antibodies) should be considered as antiviral therapy.